Perancangan Bresing Eksentris Link Pendek Pada Struktur Baja Bertingkat Di Kota Padang - Fitrah, Ridho Aidil; Al Mushoddaq, Syafiq; Kurniawan, Ruddy (Jurnal Bangunan, Konstruksi & Desain, 2025)
One of the widely implemented seismic-resistant structural systems is the Eccentrically Braced Frame (EBF) system, which combines elastic stiffness with high ductility through a specialized component known as the link. The link is designed to undergo plastic deformation and dissipate seismic energy, while the other structural elements remain within the elastic range. This mechanism makes EBF an effective solution for enhancing the seismic performance of buildings, particularly in regions with high seismic activity. This study aims to design a five-story steel structure located in Padang City by applying the EBF system using an eccentric bracing configuration with short links. The design process focuses on the primary structural elements, namely beams and columns, in accordance with applicable Indonesian national standards, specifically SNI 1729:2020. In addition, SNI 1726:2019 and SNI 1727:2020 are used for seismic and gravitational load analysis, respectively. The design of the link component refers to AISC 341-16, particularly for determining link categories and the required stiffener thickness. The results of this study include detailed drawings of the designed links based on the aforementioned codes, along with a discussion on the significance of using eccentric bracing in influencing the structural response